Evaluation of Placental Pathology in Term Low Birth Weight Babies - Sanchita, Paul; Binoy, Borah Kumar; Amilee, Gogoi (Journal of Maternal and Child Health, 2022)
Background: Low birth weight is the single most risk factor for perinatal mortality and placenta due to its importance in fetomaternal circulation plays an important role in pregnancy outcome. The present study aims to evaluate the pathological changes in the placenta in term (38-42 weeks) low birth weight babies. Subjects and Method: It is case control study done in Jorhat Medical College and Hospital during the period from June 2020 to May 2021. Consecutive sampling was done. 100 placentae were subjected to detailed gross and histological examination. Sixty placentae were from full term babies with birth weight less than 2,500g (LBW). Fourty placentae from full term babies with birth weight more than 2,500g were included in control group. Weight of the baby was taken within the 1st hour of birth and APGAR score was noted. Gross and microscopic examination of placentae was done. Statistical correlation was carried out between them by using Student t-test with SPSS software, P value <0.05 was taken as statistically significant. Results: Weight of term LBW cases placentae were lighter compared to control, diameter of the placentae in term LBW cases placenta was lesser compared to control (p= 0.045). The syncytial knot count, cytotrophoblastic cell proliferation and perivillous fibrin deposition was more in placentae of term LBW cases compared to controls (p= 0.045). Conclusion: Placental pathology among term LBW cases was high in comparison tocontrol group. The present study shows the importance of histopathological examination of the placenta to know the exact mechanism of placental dysfunction in term LBW cases. Keywords: low birth weight, perivillous fibrin deposition, syncytial knot count, cytotrophoblastic cell proliferation. Correspondence:Dr Sanchita Paul ,house no.129, karimganj, Assam. Pin: 788710. Phone: 9678801472, Email: sanchitavortex@gmail.com.